2012
DOI: 10.5402/2012/902178
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Radiotherapy and Chemotherapy in the Treatment of Primary Adult High Grade Gliomas: Assessment of Patients for These Treatment Approaches and the Common Immediate Side Effects

Abstract: Gliomas are the commonest primary brain tumours in adults. They are usually classified and graded according to the criteria by the World Health Organisation. High-grade gliomas are the most malignant primary brain tumours. Conventional therapies include surgery, radiotherapy, and chemotherapy. The tumours often demonstrate high levels of resistance to these conventional therapies, and in spite of treatment advances the prognosis remains poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 47 publications
0
10
0
1
Order By: Relevance
“…Мультимодальная терапия МГБ включает радикальное удаление опухоли мозга, лучевую терапию и химиотерапию [4]. Наиболее востребованные препараты для химиотерапии глиальных опухолей -темозоломид (ТЗМ), прокарбазин, ломустин, кармустин, нимустин, фотемустин, дакарбазин, иринотекан, этопозид, винкристин, цисплатин, карбоплатин, паклитаксел [5][6][7]. Недостатком всех этих препаратов является ограниченная способность подавлять интерфазные опухолевые клетки.…”
Section: Introductionunclassified
“…Мультимодальная терапия МГБ включает радикальное удаление опухоли мозга, лучевую терапию и химиотерапию [4]. Наиболее востребованные препараты для химиотерапии глиальных опухолей -темозоломид (ТЗМ), прокарбазин, ломустин, кармустин, нимустин, фотемустин, дакарбазин, иринотекан, этопозид, винкристин, цисплатин, карбоплатин, паклитаксел [5][6][7]. Недостатком всех этих препаратов является ограниченная способность подавлять интерфазные опухолевые клетки.…”
Section: Introductionunclassified
“…There have been many efforts to intensify radiotherapy, including the use of radiosenstizers, brachytherapy, radioactive seeds implanted in the tumor bed, and stereotactic radiosurgery in selected cases. [4] Initially the routine use of chemotherapy in addition to cranial irradiation was controversial. Individual randomized, controlled studies demonstrated no significant improvement in median survival with single agent or multiple agents chemotherapy, although a significant increase in survival was noted in a meta-analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is a predominant type of cancer that causes high mortality, and the survival rate remains relatively low even after surgery, chemotherapy or radiotherapy [ 1 ]. This low survival may result from the metastasis of cancer cells and arising resistance to drugs.…”
Section: Introductionmentioning
confidence: 99%